Arthroscopic Mumford procedure utilizing the anteromedial and Neviaser portals – a pilot cadaveric study on neurovascular structures at risk - Mohd Nasir, Mohd Nizlan; Ahmad, Azfar Rizal; Abdul Rashid, Ahmad Hisham; Hussin, Paisal; Che Hamzah, Fahrudin; Abdullah, Arifaizad; Mohd Moklas, Mohamad Aris (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2016)
Introduction: Degenerative disorder involving the acromio-clavicular joint (ACJ) is quite common especially in the elderly. One of the surgical modalities of treatment of this disorder is the Mumford Procedure. Arthroscopic approach is preferred due to its reduced morbidity and faster post-operative recovery. One method utilizes the anteromedial and Neviaser portals, which allow direct and better visualization of the ACJ from the subacromial space. However, the dangers that may arise from incision and insertion of instruments through these portals are not fully understood. This cadaveric study was carried out to investigate the dangers that can arise from utilization of these portals and which structures are at risk during this procedure. Methods: Arthroscopic Mumford procedures were performed on 5 cadaver shoulders by a single surgeon utilizing the anteromedial and Neviaser portals. After marking each portals with methylene blue, dissection of nearby structures were carried out immediately after each procedure was completed. Important structures (subclavian artery as well as brachial plexus and its branches) were identified and the nearest measurements were made from each portal edges to these structures. Results: The anteromedial portal was noted to be closest to the suprascapular nerve (SSN) at 2.91 cm, while the Neviaser portal was noted to be closest also to the SSN at 1.60 cm. The suprascapular nerve was the structure most at risk during the Mumford procedure. The anteromedial portal was noted to be the most risky portal to utilize compared to the Neviaser portal. Conclusion: Extra precaution needs to be given to the anteromedial portal while performing an arthroscopic distal clavicle resection in view of the risk of injuring the suprascapular nerve of the affected limb.